How do looking patterns, anti-fat bias, and causal weight attributions relate to adults' judgements of child weight?. (March 2023) - Evans, Elizabeth H.; Tovée, Martin J.; Hancock, Peter J.B.; Cornelissen, Piers L.
Abstract: Prevailing weight-normative approaches to health pressure adults to visually categorise children's weight, despite little understanding of how such judgements are made. There is no evidence this strategy improves child health, and it may harm children with higher weights. To understand decision-making processes and identify potential mechanisms of harm we examined perceptual and attitudinal factors involved in adults' child weight category judgements. Eye movements of 42 adults were tracked while categorizing the weight of 40 computer-generated images of children (aged 4–5 & 10–11 years) varying in size. Questionnaires assessed child-focused weight bias and causal attributions for child weight. Participants' eye movement patterns resembled those previously reported for adult bodies. Categorisation data showed a perceptual bias towards the 'mid-range' category. For higher weight stimuli, participants whose category judgements most closely matched the stimulus's objective weight had higher child-focused anti-fat bias and weaker genetic attributions for child weight – i.e, . adults who 'label' higher weight in children in line with BMI categories report more stigmatising beliefs about such children, suggesting a possible mechanism of harm. Overall, adults' judgements reflect both unalterable perceptual biases and potentially harmful attitudinal factors, calling into question the feasibility and appropriateness of public health efforts to promote visual child weight categorisation. Highlights: Adults' eye movements were tracked while they assigned weight category descriptors. The study used 40 CGI images of children aged 4–5 & 10–11 years based on 3D scans. Child-focused anti-fat bias and weight attributions influenced judgements for figures with higher weights. Intrinsic perceptual biases affected judgements for figures above and below the mid-range. Findings imply that attempts to alter adults' child weight perceptions are scientifically flawed and risk harm.